Vesicular-arbuscular mycorrhizae in coffee plantations in south of Minas Gerais State - Fernandes, Adauto B.; Siqueira, José Oswaldo (Pesquisa Agropecuaria Brasileira, 2014)
The occurrence of vesicular-arbuscular mycorrhizae in coffee plantations which occupied an area of 370.000 ha in the south of Minas Gerais State, Brazil, was studied. One hundred and fifty-four soil and plant samples were collected from coffee free plantations under production, during the summer time, for nutrient analysis. Colonization with VAM fungi was observed in every sample, with rates ranging from 9.9 to 59.4%, with mean of 27.4%. Spore density in the rhizosphere soil ranged from 1 to 120 per 50 ml, with mean of 19.6. Thirty species of VAM fungi were identified, eight of those belonging to the genus Acaulospora, twelve to Glomus, four to Scutellospora, three to Gigaspora and three to Entrophospora. In addition, two nondescribed species of Acaulospora and four of Glomus were found. Acaulospora scrobiculata, A. morrowae and A. mellea were the predominant species, occurring in more than 70% of the samples. Other species with occurrence index superior to 15% were: A. spinosa, Glomus etunicatum, G. diaphanum, G. occultum, G. fasciculatum, G. macrocarpum, G. microcarpum and Entrophospora colombiana. Microscopic examination in root segments revealed abundance of coiled hyphae, and very few arbuscules and vesicles. Although the occurrence of certain species was related to some soil and plant variables, the parameters analysed did not allow to predict the occurrence of certain species of VAM fungi in coffee agroecosystems.